The impact of the development of eating disorders in adolescents: a review - Gomes, Edna Lara Vasconcelos da Silva (2021)
The eating disorders are characterized by psychiatric condition that result in clinical complications and have as damages to health changes in eating behavior, severe distortions in body image and psychosocial agravations. The study aimed to perform a narrative review on the impact of the development of eating disorders in adolescents, the descriptors used during the search were “Eating Disorder”, “Adolescent”, “Eating Habits”. The search was carried out in the BVS, CAPES, LILACS, PUBMED and malnutrition and mortality. The prevalence has a higher incidence in females regardless of social-economic class. In this sense we emphasize the importance of early diagnosis, together with a multiprofessional team, in which the presence of a nutritionist professional specialized in the ED area is necessary.